Adaptive response of pearl oyster Pinctada fucata martensii to low water temperature stress. Issue 78 (July 2018) - Wang, Qingheng; Liu, Ya; Zheng, Zhe; Deng, Yuewen; Jiao, Yu; Du, Xiaodong
Abstract: The pearl oyster Pinctada fucata martensii is a warm-water shellfish that is sensitive to cold environments. To investigate its potential adaptation to low-temperature stress, the selected line (SL) and based population (BP) were sampled to undergo transcriptome sequence. Results of transcriptome analysis showed 572 significant differentially expressed genes. The typical HSP70 and HSP40 exhibited the polar expression model in the two groups. Meanwhile, the related genes that involved in energy release mediated by oxidative phosphorylation and the biosynthesis of unsaturated fatty acid were increased in the SL. The apparent enrichment of different expressed genes in amino acid metabolism indicated that the small molecule system with amino acids was one of the main regulator for low-temperature stress. The different expressions of immune-related and lysosome protein encoding genes also reflected the variation of immunity in the two groups and indicated that it could affect the adaptation ability in different temperature. In addition, the similar trends of different expression of typical genes between two groups were obtained by using RNA-seq and qRT-PCR. These results suggested that multi-system adjustments are involved in the processes of low water temperature stress in pearl oyster, providing insights into the response systems of shellfish to acclimatise with ambient environment change. Highlights: HSP70 and HSP40 exhibited the polar expression model in the two populations. Biosynthesis of unsaturated fatty acid and energy release was increased in the SL. The small molecular system with amino acids might play a key role in cold stress. Lysosome and immune function could influence the low temperature resistance.